The Impact of Parental Divorce on Children's Psychology in Case Study on Students of SMK Muhammadiyah 2 Surabaya - Su darti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
Parental divorce affects the children's psychology influences on the learning process or their education at school. This study aims: firstly, to know the various factors causing parental divorce of SMK Muhammadiyah 2 Surabaya. Secondly, how the strategies of SMK Muhammadiyah 2 Surabaya in handling student problem caused by parental divorce are. Thirdly, How the effect of parental divorce to children’s psychology of SMK Muhammadiyah 2 Surabaya is. Type of research in this research was qualitative description approach implemented in SMK Muhammadiyah 2 Surabaya. Data collection in this research was observation, interview and documentation. Data analysis used in this research was to reduce data, display data, findings of this research can be concluded: First: The factor causing divorce of parents is disharmony in the household. Disharmony caused by various things, among others, economic factors and the existence of a third person (infidelity). Both School strategies in dealing with student’s problems caused by parental divorce call the students ongoing counseling. Conducting teamwork with homeroom teacher and student’s best friend to monitor the progress of their attitude, encouraging and being given religious guidance so that students can accept reality with sincerity. Students are advised to participate in extracurricular activities in order to reduce the sad, more caring heart. Third The impact of parental divorce is that children's achievement in school is decreased or they become more frequent to quiet, angry, shy, idle and naughty loners. Keywords: Impact, Divorce, Children’s psychology